Rapid chloride penetration on high performance fly ash incorporated silica fume concrete (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Mechanical and durability properties of fly ash incorporated high performance silica fume concretes are discussed with respective to the obtained experimental results. Concrete specimens are prepared at the water-to-binder ratio of 0.28.  The effect of inclusion of various percentages of silica fume (4%, 8%, 10% and 12%) on the workability, the Compressive strength and the Rapid chloride penetration, according to ASTM C 1202  are determined and compared with the reference mix in which 12% of fly ash is kept constant as cement replacement material. The consumption of alternative  fine aggregate is an accepted step towards solving part of the depletion of natural aggregate and hence sand was substituted with M-sand of 50 %. Total binder content was kept constant as  600 kg/m3 for all the concrete mixtures. Result show that the combination of 8 to 10 % silica fume and 12% fly ash increase the  strength  of concrete, but beyond 10% of silica fume with 12% of fly ash combination the compressive strength get decreased. The incorporation of  silica fume and fly ash in the concrete mixtures, increased the resistance to chloride ions while an increasing percentage of silica fume in ternary mix and shaped the concretes with very low permeability - high performance.